Preliminary Study: Characterization of UHMWPE and PP Polymer for Extrudability of PP/UHMWPE Composite to FFF Process - Raman, Fakrul Nur Aiman; Kamarudin, Khairu; Shufeng Sun; Shaari, Muhammad Farid; Roslan, Mohd Nazrul; Ahmad, Aznizam; Mustaffa, Norrizal; Muhammad Syafiq Mohd Khairuddin (Journal of Advanced Industrial Technology and Application, 2024)
Ultra-high molecular weight polyethylene, or UHMWPE, is a thermoplastic semicrystalline polymer with outstanding wear resistance, low friction coefficient, and mechanical qualities. It also can exhibits powerful resistance to corrosive substances. Even Ultra-high molecular weight polyethylene (UHMWPE) has unique characteristics, but it features an extremely low melt flow rate (MFR) of near zero, which renders it unsuitable for processing using traditional polymer processes. Thus, PP is one of the most potential plasticizers for increasing the extrudability of UHMWPE-based composites. PP, commonly known as Polypropylene, is a thermoplastic polymer that is widely used in many industry sector. It is made from the monomer propylene using chain-growth polymerization. However, there is a problem where the chemical incompatibility of the PP-UHMWPE composites makes the composite is difficult to manufacture. As a result, the intent of this research is to examine the characteristics of both materials in order to acquire a better knowledge of the requirements and to present a deeper insight into these two materials in order to increase the extrudability of PP-UHMWPE composite for Fused Filament Fabrication (FFF). The characterization procedure comprises the morphological and flow properties, thermal behavior and stability, and crystallinity of UHMWPE and PP in powder and granular form, respectively. The research illustrates the feature for both polymer behavior that is influenced by particle shape. This paper's findings were utilized to manufacture the extrudability of PP-UHMWPE composites using FFF as a bone repair implant.